2001
DOI: 10.1007/pl00001944
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Incisor Mobility after Insertion of Canine-to-Canine Lingual Retainers Bonded to Two or to Six Teeth A Clinical Study

Abstract: The results showed that bonded retainers had a negative impact on the damping properties of the periodontal tissue and thus in the broader sense on tooth mobility. Tooth mobility decreased with the number of teeth to which the retainer was bonded but remained, as in the control group, within the physiologic range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 7 publications
4
14
0
5
Order By: Relevance
“…According to Watted's study of 60 patients, separated in 3 groups (two of which are with fixed retainer and one with removable retainer) the dental mobility reduces with the number of teeth, fixed in the retainer [21]. This conclusion was supported by a study of Stormann, which recruited 103 patients [22].…”
Section: Discussionmentioning
confidence: 96%
“…According to Watted's study of 60 patients, separated in 3 groups (two of which are with fixed retainer and one with removable retainer) the dental mobility reduces with the number of teeth, fixed in the retainer [21]. This conclusion was supported by a study of Stormann, which recruited 103 patients [22].…”
Section: Discussionmentioning
confidence: 96%
“…patients with fixed retainers during the first 6 months of retention. Few studies 5,17 have investigated the impact of removable retainers on periodontal health. Heier et al 5 evaluated the differences between fixed and removable retainers, but only the segment from canine to canine was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…With a total of 60 participants, divided into 3 equal groups (2 groups with mandibular bonded retainers and one control group with removable retainers), the study results revealed that tooth mobility decreased with the number teeth bonded to the retainer [20].…”
Section: IIImentioning
confidence: 99%